2011
DOI: 10.1016/j.ijggc.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary cost and engineering estimate for desalinating produced formation water associated with carbon dioxide capture and storage

Abstract: The risk associated with storage of carbon dioxide in the subsurface can be reduced by removal of a comparable volume of existing brines (e.g., Buscheck et al., 2011). In order to avoid high costs for disposal, the brines should be processed into useful forms such as fresh and low-hardness water. We have carried out a cost analysis of treatment of typical subsurface saline waters found in sedimentary basins, compared with conventional seawater desalination. We have also accounted for some cost savings by utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…These differences allowed us to set the technical limit at 85 g/L instead of 50 g/L. The research found in Bourcier, et al (2011) confirmed our assumption that RO membranes can treat brines up to 85 g/L at lower recovery fractions, high brine extraction volumes, and with anti--scale pretreatment.…”
Section: Reverse Osmosis Treatmentsupporting
confidence: 70%
See 2 more Smart Citations
“…These differences allowed us to set the technical limit at 85 g/L instead of 50 g/L. The research found in Bourcier, et al (2011) confirmed our assumption that RO membranes can treat brines up to 85 g/L at lower recovery fractions, high brine extraction volumes, and with anti--scale pretreatment.…”
Section: Reverse Osmosis Treatmentsupporting
confidence: 70%
“…RO is a mature technology that is economic for desalinization of saline groundwater where TDS is low and where freshwater demand is high Bourcier et al 2011). Using RO to treat water with TDS greater than 50 g/L is rarely practiced by desalination plants for technical and economic reasons.…”
Section: Reverse Osmosis Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated with numerical simulations that extraction of brine from the lower portion of the storage formation, from locations progressively further from the center of injection, can counteract the buoyancy force that drives CO 2 to the top of the storage formation, thereby Page 4 allowing for higher storage efficiency and improved injectivity. Brine extraction may also create economic value via beneficial use of treated brine (e.g., Bourcier et al, 2011;Maulbetsch and DiFillipo, 2010) or may reduce other costs for CO 2 storage, such as those related to compression, liability insurance, site characterization, or monitoring (Buscheck, 2011b).On the other hand, brine extraction requires pumping, transportation, possibly treatment, and disposal of substantial volumes of extracted brackish or saline water, which can be technically challenging and expensive. evaluated the cost of extracted water management based on analogs from water production in oil and gas operations.…”
mentioning
confidence: 99%
“…Membrane treatment is one mature technology used by water utilities and other industries throughout the US. RO desalination is typically used to treat seawater (around 35 g/L), but we assumed RO was feasible for saline groundwater with TDS less than 90 g/L at low recovery rates and in water scarce regions Bourcier et al, 2011). This assumption may be optimistic given current RO membrane technology, but we assumed the technology will improve over time.…”
Section: Freshwater Water Productionmentioning
confidence: 99%